Meta Sintesis: Penggunaan E-Portofolio sebagai Asesmen Alternatif dalam Pembelajaran Biologi - Ma’fud, Sukhrul; Abidin, Zaenal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The digital transformation in education has driven a paradigm shift in assessment, from traditional forms to technology-based alternatives such as e-portfolios. The purpose of this study is to analyze the implementation patterns of e-portfolios in biology learning, evaluate their impact on student competency development, and identify implementation barriers. The research method used a meta-synthesis approach to English-language articles published between 2020 and 2025 from the Google Scholar database. A search using the combination of keywords